Improved simple T-cannula technique to facilitate surgery and daily skin care of growing pigs. (23rd March 2020) - Metzler-Zebeli, Barbara U; Rosenfelder-Kuon, Pia; Brehm, Helga; Eklund, Meike; Mosenthin, Rainer
Abstract: In order to further increase the stability of the cannula behind the ribs and to facilitate cannula exteriorization in growing pigs, the present study aimed to evaluate whether elongation of the cannula flange could increase the stability of the cannula behind the ribs and to develop a tool to improve the exteriorization of the cannula through the ribs. Moreover, it was assessed whether a special skin protection paste and soft polyurethane foam material used in daily skin care could prevent erythema around the fistula. The feasibility of both, the modified simple T-cannula and daily skin care procedure, was evaluated in a digestibility experiment. Simple T-cannulae were made of high-molecular-weight polyethylene and inserted into the distal ileum of eight growing pigs (average body weight at surgery 30 kg). Modifications in the cannula design included a longer flange (11 cm) that was narrowed from the center to the ends and a bending of the flange to adapt it to the curve of the costal arch. In order to reduce the damage to the thread on the outer cannula barrel during surgery, a special surgical plug in conjunction with a screw thread on the inside of the barrel was developed. With respect to the daily cleaning of the fistula, a special skin protection paste was applied on the skin around the fistula to create a waterproof film that entirely sealed the skin. Additionally, foam material was inserted between the retaining ring and the skin to absorb the leaking digesta. Monitoring of the pigs throughout the trial showed that modifications in cannula design proved to be useful as they facilitated exteriorization of the cannula through the ribs and stability of the cannula behind the ribs. Moreover, the use of the skin protection paste and foam material during postsurgical treatment of growing pigs effectively prevented skin irritation around the flank area.